2021
DOI: 10.1002/hep4.1745
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 in Liver Disease Progression

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a novel coronavirus that causes coronavirus disease 19 , which has infected millions of people worldwide in only a few months.A minority, but significant number, of infected individuals require hospitalization and intensive care. From the start of this new virus pandemic, it was apparent that obese and/or diabetic individuals had a bad prognosis for COVID-19 progression, strongly suggesting an association between liver disease and severe COVID-19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 121 publications
(242 reference statements)
1
31
0
6
Order By: Relevance
“…Using the MELD score, clinicians can determine the level of care for cirrhotic patients, especially those infected with COVID-19 [10,11]. While the existing literature is currently limited, studies have shown that those with chronic liver disease, such as our patient, will have elevated MELD scores and suffer increased hepatic and pulmonary complications when infected with COVID-19 [4,10,11]. Specifically, the mortality rate in patients infected with COVID-19 with preexisting alcoholic liver disease is upwards of 1.8 times higher than those without the preexisting condition.…”
Section: Discussionmentioning
confidence: 99%
“…Using the MELD score, clinicians can determine the level of care for cirrhotic patients, especially those infected with COVID-19 [10,11]. While the existing literature is currently limited, studies have shown that those with chronic liver disease, such as our patient, will have elevated MELD scores and suffer increased hepatic and pulmonary complications when infected with COVID-19 [4,10,11]. Specifically, the mortality rate in patients infected with COVID-19 with preexisting alcoholic liver disease is upwards of 1.8 times higher than those without the preexisting condition.…”
Section: Discussionmentioning
confidence: 99%
“…Also, membrane less SARS-CoV-2 vesicles have been recognized in the hepatocyte's cytoplasm of two COVID-19 patients along with high expression of liver damage markers [184]. The SARS-CoV-2 mediated hypoxia and cytokine storm could also potentiate liver injury [179]. Meanwhile some other studies reported that antiviral drugs used for the support of COVID-19 patients could also induce hepatotoxicity.…”
Section: Liver Diseasementioning
confidence: 95%
“…Generally the chronic liver disease (CLD) is correlated with immune dysregulation and inflammation, which may present a greater risk of COVID-19 mediated pathogenesis [179]. Recent shreds of evidence support the cross talk between SARS-CoV-2 infection and CLD.…”
Section: Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Emphasising the fact that for COVID‐19 patients’ appropriate interventions and liver function repair is necessary. The chronic liver conditions also carry greater risk and adverse risk and needs special interventions 40 …”
Section: Introductionmentioning
confidence: 99%